Risk factor investigation for hip dislocation after periacetabular tumour resection and endoprosthetic reconstruction via thin-slice CT-based 3D model. (1st October 2022) - Qu, Hao; Mou, Haochen; Wang, Keyi; Tao, Huimin; Huang, Xin; Yan, Xiaobo; Lin, Nong; Ye, Zhaoming
Abstract : Aims: Dislocation of the hip remains a major complication after periacetabular tumour resection and endoprosthetic reconstruction. The position of the acetabular component is an important modifiable factor for surgeons in determining the risk of postoperative dislocation. We investigated the significance of horizontal, vertical, and sagittal displacement of the hip centre of rotation (COR) on postoperative dislocation using a CT-based 3D model, as well as other potential risk factors for dislocation. Methods: A total of 122 patients who underwent reconstruction following resection of periacetabular tumour between January 2011 and January 2020 were studied. The risk factors for dislocation were investigated with univariate and multivariate logistic regression analysis on patient-specific, resection-specific, and reconstruction-specific variables. Results: The dislocation rate was 13.9% (n = 17). The hip COR was found to be significantly shifted anteriorly and inferiorly in most patients in the dislocation group compared with the non-dislocation group. Three independent risk factors were found to be related to dislocation: resection of gluteus medius (odds ratio (OR) 3.68 (95% confidence interval (CI) 1.24 to 19.70); p = 0.039), vertical shift of COR > 18 mm (OR 24.8 (95% CI 6.23 to 128.00); p = 0.001), and sagittal shift of COR > 20 mm (OR 6.22 (95% CI 1.33 to 32.2); p = 0.026). Conclusion: Among the 17 patients who dislocated, 70.3% (n = 12) were anterior dislocations. Three independent risk factors were identified, suggesting the importance of proper restoration of the COR and the role of the gluteus medius in maintaining hip joint stability. Cite this article: Bone Joint J 2022;104-B(10):1180–1188.